Relationship between motivation for physical exercise and women's quality of life - Naiara Santana Graciano; Daniel Vicentini de Oliveira; Yara Lucy Fidelix; Ana Luiza Barbosa Anversa; José Roberto Andrade do Nascimento Júnior; Gabriel Lucas Morais Freire; Rose Mari Bennemann; Fábio Ricardo Acencio (Hospital de Clínicas de Itajubá, 2021)
Objective: To identify motivational factors for the practice of physical exercises and their relationship with the quality of life (QoL)of women. Methods: A cross-sectional study, conducted with 48 women practicing exercise in gyms aged between 19 and 59 years and with a mean age of 39.4 ± 11.7 years. Exercise Motivations Inventory (EMI-2) and WHOQOL-Bref were used as instruments. The data were analyzed using the Kolmogorov-Smirnov tests, homogeneity of Levene's variances, independent t-test, and Pearson's correlation (p < 0.05). Results: Older women are more motivated to exercise for health rehabilitation. The youngest had a higher score in the physical domain of quality of life. There was a significant, positive, and weak correlation of the physical domain with weight control (r = 0.24), appearance (r = 0.33), a weak and negative correlation of the physical domain with health rehabilitation (r = -0,33), a positive and weak correlation of the social domain with physical conditioning (r = 0.23), and a positive and weak correlation of the general QoL score with weight control (r = 0.23). Conclusion: The main motivational factor for the practice of physical exercise was preventing diseases, especially in the group of older women. Younger women had a better perception of the physical QoL domain, and correlations between some domains of QoL and motivation were observed.